The tell-tale heart: heart rate fluctuations index objective and subjective events during a game of chess - Leone, Maria J.; Petroni, Agustin; Fernandez Slezak, Diego F.; Sigman, Mariano (Frontiers in Human Neuroscience, 2012)
During a decision making process, the body changes. These somatic changes have been related to specific cognitive events and also have been postulated to assist decision making indexing possible outcomes of different options. We used chess to analyze heart rate (HR) modulations on specific cognitive events. In a chess game, players have a limited time-budget to make about 40 moves (decisions) that can be objectively evaluated and retrospectively assigned to specific subjectively perceived events, such as setting a goal and the process to reach a known goal. We show that HR signals events: it predicts the conception of a plan, the concrete analysis of variations or the likelihood to blunder by fluctuations before to the move, and it reflects reactions, such as a blunder made by the opponent, by fluctuations subsequent to the move. Our data demonstrate that even if HR constitutes a relatively broad marker integrating a myriad of physiological variables, its dynamic is rich enough to reveal relevant episodes of inner thought.